THE INFLUENCE OF BRAND IMAGE AND STORE ATMOSPHERE ON CONSUMER PURCHASE INTEREST OF KOPI PETIK JL.PEMBANGUNAN KM.12 - Rio Fahmi Huseini Ritonga; Riza Fanny Meutia; Hery Syahrial; Nindya Yunita (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This article aims to determine the influence of Lifestyle on Purchasing Decisions in Dagi This study aims to determine the influence of Brand image on Consumer Purchase Interest in Kopi Petik Jl.Pembangunan km.12. To determine the influence of Store atmosphere on Consumer Purchase Interest in Kopi Petik Jl.Pembangunan km.12. To determine the influence of Brand image and Store atmosphere on Consumer Purchase Interest in Kopi Petik Jl.Pembangunan km.12. The sampling technique used in this study is probability sampling, the number of samples in this study was 98 consumers who made purchases at Kopi Petik Jl.Pembangunan KM.12. The data analysis technique used is descriptive analysis technique and statistical analysis technique. The method of data collection through distribution, namely conducting searches and distributing questionnaires to consumers who make purchases at Kopi Petik Jl.Pembangunan KM.12. The results of this study indicate Based on the results of the study, it shows that partially the Brand Image variable has a positive and significant effect on consumer purchase interest in Kopi Petik Jl. Pembangunan Km.12. Based on the results of the study, it shows that partially the store atmosphere variable has a positive and significant effect on consumer purchasing interest in Kopi Petik Jl. Pembangunan Km.12. Simultaneously, there is a positive and significant effect on the brand image and store atmosphere variables on consumer purchasing interest in Kopi Petik Jl. Pembangunan Km.12.